IMPLICATIONS OF SUDDEN DEATH IN CHAGAS DISEASE - Mendoza, Ivan; Moleiro, Federico; Marques, Juan; Guerrero, Júlio; Matheus, Álvaro; Rodriguez, Freddy; Rodriguez, Ana; Britto, Ivan Mendoza; Luna, António Bayes de; Castellanos, Agustin (Revista de Patologia Tropical / Journal of Tropical Pathology, 2007)
American Trypanosomiasis or Chagas disease is an important problem of publichealth affecting 20 million people in Latín America. It is caused by the flagellate parasiteTrypanosoma cruzi. Chronic progressivo heart disease develops in approximately 20 to 40% ofinfected persons. Chagas heart disease is one of the leading causes of sudden death aftercoronary heart disease. Approximately, half of the patients with Chagas heart disease diedsuddenly. The mechanism of sudden death in Chagas disease include ventricular fibrillation ortachycardia, severe bradyarrhythmia, embolic complication and spontaneous ventricular rupture.Proarrhythmia is common due to the coexistence of heart failure and multiple electrophysiologicabnormalities including sinus node dysfunction, intraventricular and atrioventricular conductionabnormalities, severe multiform ventricular arrhythmia, abnormal Q waves and altered STsegment and T wave abnormalities. Thus the ventricular arrhythmias of Chagas heart disease areone of the most demandíng models on which an antiarrhythmic drug can be tested. Chagas heartdisease is now a widen problem as a result of immigration. The transmíssion of Chagas diseasevia blood transfusion is not confmed to countries where the disease is endemic. The migration ofpersons infected by Trypanosoma cruzi poses a public health problem even for countries wherethe disease is not transmitted by vector. Most of the Latin American immigrant with Chagasheart disease living in United States and Europe are either undiagnosed or misdiagnosed ashaving either idiopathic cardiomiopathy or coronary artery disease.